Kecerdasan Emosional/Emotional Intelligence (EQ) - Putri Mukhlisa; Sindi Yohenda; Ulfa Yanti; Linda Yarni (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Emotional intelligence is a major focus in modern psychological studies, and research continues to expand to understand its aspects, factors, and benefits. This literature review explores the dimensions of emotional intelligence which include understanding one's emotions, managing emotions, empathy, and social skills. Factors that influence emotional intelligence, such as social environment, life experiences, and genetics, are an important focus. The benefits of emotional intelligence include improved psychological well-being, better interpersonal relationships, and superior academic and professional performance. This article aims to understand and develop a person's emotional intelligence. The method in this article uses literature study, namely a data collection method by understanding and studying theories from various literature related to research. This article details the contribution of various studies to enriching the understanding of emotional intelligence, providing a basis for the development of more effective training programs. in increasing individual emotional intelligence.